PENGARUH IKLAN TELEVISI SAMSUNG GALAXY S4 TERHADAP KEPUTUSAN MEMBELI MASYARAKAT EKONOMI MENENGAH KEATAS DI KECAMATAN UJUNG BATU - PRATAMA, NANDA; ", RUMYENI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research purpose is to know the size of effect of Samsung Galaxy SIV advertising on toward the decision of middle upto high economy class in Ujungbatu Subdistrict. Populations in this research are the society of Ujungbatu Subdistrict as the respondent. Respondent selection process as an object of the research is based on society appraisal in their decision to buy Samsung Galaxy SIV which effected by the advertising. By using Purposive Sampling Technique, from the Slovin Equation, thus this research gains 81 people as respondents. Collecting Data Method is by field research using questioner, inquiry and library research. Data Analysis that used is data analysis using software program SPSS version 16 (validation test and reliability test) and apply likert scaling on the questioner. The result of the research shows that from simple regression analysis (r) the relation between TV advertise (r) is 0.830 and r2(r-square) is 0.690 (69%). These values describe that the effect of advertise on television has a strong effect toward buying decision as much as 69%. The effect of advertise on television trough music or jingle, story board, copy or script, endorsement, slogan, logo has affection for consumer. They get a feeling that the Samsung Galaxy SIV advertise is about a good product, competent. Among respondent above, better response comes after the advertise of Samsung Galaxy SIV in Ujungbatu Subdistrict. Whereas buying decision based on AIDDA theory toward Samsung Galaxy Product is affected after watching advertise on television, valuing and learning the information from that quality product and so it produce a high confidence to buy Handphone Samsung Galaxy SIV.Keywords : Influence, Advertise, Samsung Galaxy S4